Cover Image. (8th June 2018) - Simmhan, Yogesh; Ravindra, Pushkara; Chaturvedi, Shilpa; Hegde, Malati; Ballamajalu, Rashmi
Abstract : The cover image, by Yogesh Simmhan et al., is based on the Experience Report Towards a data‐driven IoT software architecture for smart city utilities, https://doi.org/10.1002/spe.2580 . Photo Credit: Yogesh Simmhan, Pushkara Ravindra, Shilpa Chaturvedi, Malati Hegde, and Rashmi Ballamajalu